Youth Entrepreneurial Intention: Theory of Planned Behaviour and Social Cognitive Theory - Aflit Nuryulia Praswati; Nelly Purnama Sari; Sri Murwanti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2022)
This study adopted the Theory of planned behavior (Ajzen, 1991) and Social cognitive theory (Bandura, 1986) to examine student interest in entrepreneurial activities (entrepreneurial intention). The sample taken is 100 students who have received introductory entrepreneurship or business courses. The results of the study were analyzed using the analysis of the outer model and inner model with the help of SmartPLS 3.0 software. The results showed that self-efficacy had a significant positive effect on entrepreneurial intentions, while subjective norms and attitudes had no significant effect on entrepreneurial intentions. Entrepreneurship education shows a significant positive effect on self-efficacy, and does not significantly affect entrepreneurial intentions, but when self-efficacy mediates the relationship between the two, the analysis shows that entrepreneurial education can significantly affect entrepreneurial intentions. The moderating variable of motivation is proven not to be able to strengthen or weaken the relationship between entrepreneurship education and self-efficacy on entrepreneurial intentions.